Pemberdayaan UMKM Desa Kebondowo Kecamatan Banyubiru Kabupaten Semarang di Masa Pandemi Covid-19 dengan Pelatihan Pembuatan Face Shield - Kholidin Kholidin; Rachmanda Cahya Patria (GOTAVA, 2023)
The Covid-19 pandemic has a major impact on Indonesian society, including the Small and Medium Enterprises (MSMEs) sector. According to data, as many as 48.6% of MSMEs had to be closed due to a significant decrease in demand. Likewise, MSMEs in Kebondowo Village, Banyubiru District, Semarang Regency have had to stop production and lay off workers due to this pandemic. This community service activity aims to empower MSMEs to revive their business during the Covid-19 pandemic. The method used to obtain the objective is training in producing face shields by utilizing ergonomic materials, as well as skills and tools that are already owned by MSMEs. The result of this community service activity is that MSMEs can revive their business by producing and promoting the face shield of their own production.